Clinical neuroendocrinology - Fliers, Eric (Handbook of clinical neurology, 2014)
Clinical Neuroendocrinology, a volume in the Handbook of Clinical Neurology Series gives an overview of the current knowledge in the field of clinical neuroendocrinology. It focuses on the pathophysiology, diagnosis, and treatment of diseases of the hypothalamus and the pituitary gland. It integrates a large number of medical disciplines, including clinical endocrinology, pediatrics, neurosurgery, neuroradiology, clinical genetics, and radiotherapy. Psychological consequences of various disorders and therapies, as well as therapeutic controversies, are discussed. It is the first textbook in th.